Treatment and outcome of autoimmune hepatitis: Audit of 28 UK centres. (28th March 2022) - Gordon, Victoria; Adhikary, Ratul; Appleby, Victoria; Das, Debasish; Day, James; Delahooke, Toby; Dixon, Selena; Elphick, David; Hardie, Claire; Heneghan, Michael A.; Hoeroldt, Barbara; Hooper, Patricia; et al.
Abstract: Background: With few data regarding treatment and outcome of patients with AIH outside of large centres we present such a study of patients with AIH in 28 UK hospitals of varying size and facilities. Methods: Patients with AIH were identified in 14 University and 14 District General hospitals; incident cases during 2007–2015 and prevalent cases, presenting 2000–2015. Treatment and outcomes were analysed. Results: In 1267 patients with AIH, followed up for 3.8 (0–15) years, 5‐ and 10‐year death/transplant rates were 7.1 ± 0.8% and 10.1 ± 1.3% (all‐cause) and 4.0 ± 0.6% and 5.9 ± 1% (liver related) respectively. Baseline parameters independently associated with death/transplantation for all causes were: older age, vascular/respiratory co‐morbidity, cirrhosis, decompensation, platelet count, attending transplant centre and for liver related: the last four of these and peak bilirubin. All‐cause and liver‐related death/transplantation was independently associated with: non‐treatment with corticosteroids, non‐treatment with a steroid‐sparing agent (SSA), non‐treatment of asymptomatic or non‐cirrhotic patients and initial dose of Prednisolone >35 mg/0.5 mg/kg/day (all‐cause only), but not with type of steroid (Prednisolone vs. Budesonide) or steroid duration beyond 12 months. Subsequent all‐cause and liver‐death/transplant rates showed independent associations with smaller percentage fall in serum ALT after 1 and 3 months, but not with failure to normalise levels over 12 months. Conclusions: We observed higher death/transplant rates in patients with AIH who were untreated with steroids (including asymptomatic or non‐cirrhotic subgroups), those receiving higher Prednisolone doses and those who did not receive an SSA. Similar death/transplant rates were seen in those receiving Prednisolone or Budesonide, those continuing steroids after 12 months and patients attaining normal ALT within 12 months versus not.